DAMPAK REHABILITASI KAWASAN WISATA EKOSISTEM MANGROVE TERHADAP MASYARAKAT DI KELURAHAN BERBAS PANTAI KOTA BONTANG T - Ardiansyah; Said Abdussyahid; Nurul Ovia Oktawati (Jurnal Pembangunan Perikanan dan Agribisnis, 2016)
purpose of this study was to determine the impact rehabilitation of mangrove ecosystems. This study conduced during amonth in Berbas Pantai Village, Bontang District. The result showed that the negative and pasitivr impacts of the rehabilitation activites. The positive impact the rehabilitation is the area used as torist are and braek water erosion. Eventough the high cost and lack of success in the area for rehabilitation direct positive impact on the community as a tourist areas in based on the regression model and obtained values Rp1.310.168 the average value of visitor to the mangrove ecosystem in 2015 amounted 12,375 and the numbers trvel to mangrove ecosystem result is obtained Rp4.632.382 hectare/year.Indirect Use Value (IUV) are the benefits of mangrove ecosystems indirectly. The physical benefits are benefits of the mangrove ecosystem as a drag abrasion estimated by replacement cost of manufacture concrete beach for Breakwater (break water). Negative the impactofthis activityisa considerable costforthe rehabilitation of mangrove ecosystems that this Rp21.795.000 of replanting mangrove ecosystem. Then, from the manufacture of garden toursand a lack of supervision of the local government for the sustainability of this region. The total value of mangrove showed Rp-16.301.380 This shows the magnitude of the negative impacton the value of compare positive impact on mangrove ecosystem rehabilitation.